Fundus examination of 199 851 newborns by digital imaging in China: a multicentre cross-sectional study. Issue 12 (17th August 2018) - Tang, He; Li, Na; Li, Zhan; Zhang, Meiju; Wei, Meirong; Huang, Changbing; Wang, Jihong; Li, Fuxin; Wang, Hong; Liu, Zijiang; He, Liying; Cheng, Yangyang; et al.
Abstract : Background: The prevalence of ocular abnormalities of newborn in China has seldom been reported. To report the implementation of digital imaging in ocular screening of all newborns in multiple centres in China and to describe the abnormal findings of fundus examination, we did the cross-sectional study. Methods: Fundus examinations were performed on newborns within the 42 days after birth using a RetCam wide-field digital imaging system. Digital images of the posterior pole, superior, nasal and temporal retinal fields of each participant were taken. All newborns were from eights centres across China from January 2009 to July 2017. Results: A total of 199 851 newborns were included in the study. We detected 18 198 (9.11%) abnormal cases. The most frequent abnormality was severe retinal haemorrhage (RH) found in 12 810 cases (6.41%). The other anomalies included familial exudative vitreoretinopathy, retinopathy of prematurity, abnormal fundus pigmentation, subconjunctival haemorrhage, choroidal coloboma, idiopathic retinal venous tortuosity, exudative changes and other anomalies with uncertain identities. Conclusion: This large-scale study of newborn fundus examination showed a relatively high prevalence of ocular abnormalities. Hundreds of neonates with rare disorders that severely impair ocular health were also detected at an early age. The long-term impact of other anomalies including RHs on the ocular system should be investigated by a perspective study. Our study suggested that fundus examination of newborns can play a beneficial role in ocular health.